2020
DOI: 10.3390/ph13070144
|View full text |Cite
|
Sign up to set email alerts
|

Loss of miR-101-3p Promotes Transmigration of Metastatic Breast Cancer Cells through the Brain Endothelium by Inducing COX-2/MMP1 Signaling

Abstract: Brain metastases represent one of the incurable end stages in breast cancer (BC). Developing effective or preventive treatments is hampered by a lack of knowledge on the molecular mechanisms driving brain metastasis. Transmigration of BC cells through the brain endothelium is a key event in the pathogenesis of brain metastasis. In this study, we identified miR-101-3p as a critical micro-RNA able to reduce transmigration of BC cells through the brain endothelium. Our results revealed that miR-101-3p exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 54 publications
0
33
0
Order By: Relevance
“…In another study, brain metastatic cancer cells were shown to release microRNA-181c-containing extracellular vesicles capable of destructing the BBB [63]. In addition, we recently demonstrated that loss of miR-101-3p promote transmigration of BC cells by inducing COX-2/MMP1 signaling [64]. These observations point to miRNA as promising therapeutic targets, however, more research is still needed to unravel the panel of specific micro-RNA profiles that regulate the different steps of breast cancer brain metastatic cascade and that are suitable as therapeutic agents to suppress or prevent BM.…”
Section: Discussionmentioning
confidence: 92%
“…In another study, brain metastatic cancer cells were shown to release microRNA-181c-containing extracellular vesicles capable of destructing the BBB [63]. In addition, we recently demonstrated that loss of miR-101-3p promote transmigration of BC cells by inducing COX-2/MMP1 signaling [64]. These observations point to miRNA as promising therapeutic targets, however, more research is still needed to unravel the panel of specific micro-RNA profiles that regulate the different steps of breast cancer brain metastatic cascade and that are suitable as therapeutic agents to suppress or prevent BM.…”
Section: Discussionmentioning
confidence: 92%
“…In our study, we found high expression in the cavernous and differentiated histological subtypes. Claudin-5 could be used as a marker with greater sensitivity and could also be of diagnostic value in the differential diagnosis of canine HSAs from other sarcomas with hemorrhage or increased vascularization [16,17,[32][33][34]. Claudin-5 might also represent an interesting prognostic marker for canine HSA metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…MMPs not only promote tumour cell invasion and proliferation by destroying the ECM barrier but also act on cell signalling in a variety of ways 46 . One study reported a link between MMP1 and brain metastasis in breast cancer, 47 and several studies have examined the influence of MMP11 expression on the prognosis of patients with breast cancer 48,49 . The relationship between MMP13 and metastatic breast cancer has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%